Direct oxygen isotope effect identifies the rate-determining step of electrocatalytic OER at an oxidic surface. Issue 1 (December 2018) - Haschke, Sandra; Mader, Michael; Schlicht, Stefanie; Roberts, André; Angeles-Boza, Alfredo; Barth, Johannes; Bachmann, Julien
Abstract Understanding the mechanism of water oxidation to dioxygen represents the bottleneck towards the design of efficient energy storage schemes based on water splitting. The investigation of kinetic isotope effects has long been established for mechanistic studies of various such reactions. However, so far natural isotope abundance determination of O2 produced at solid electrode surfaces has not been applied. Here, we demonstrate that such measurements are possible. Moreover, they are experimentally simple and sufficiently accurate to observe significant effects. Our measured kinetic isotope effects depend strongly on the electrode material and on the applied electrode potential. They suggest that in the case of iron oxide as the electrode material, the oxygen evolution reaction occurs via a rate-determining O−O bond formation via nucleophilic water attack on a ferryl unit. Understanding reaction mechanisms is crucial for catalyst design. Here, natural-abundance isotope quantifications of O2 yield mechanistically significant reaction kinetic isotope effects for water oxidation over metal oxide electrodes, the bottleneck step of water electrolysis.